Identification of business ideas for creation of company in the displaced population of Florencia, Colombia - Garrido-Hurtado, Dora Lilia; Valderrama-Cardona, Enna Alexandra (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The aim of this paper is to identify business ideas in the displaced population in the city of Florencia, Colombia, as a vital input to the generation of viable enterprises. It was worked with 56 people of the residential La Bocana of Florencia – Caquetá, which 32% were men and 68% women. It was applied a survey that allowed to recognize the business ideas, as well as the actions they have taken to implement them. The results show that 75% of respondents have thought in creating a business. Most relevant business ideas are: dressmaking, grocery store, and handicrafts, which are in concord with the families conformations, because these are mono-parenting, headed by women. Similarly, business ideas are related with the trade dynamics of municipality, where trade is a fundamental part of its economy, followed by the small industry of guadua-work, wood, and indigenous handicrafts. In this regard, it is appropriate to use the business plan as a tool that allows the generation of viable enterprises, as an alternative for improving the economic situation in a population as vulnerable as the displaced people.